2018
DOI: 10.7759/cureus.2131
|View full text |Cite
|
Sign up to set email alerts
|

Visual and Refractive Outcomes of Topography-guided Laser-assisted In Situ Keratomileusis in Virgin Eyes

Abstract: IntroductionWe wanted to assess the efficacy, predictability, and stability of topography-guided, laser-assisted in situ keratomileusis (TGL) on normal untreated eyes with a preoperative best corrected visual acuity (BCVA) of 20/20.MethodsThis was a retrospective, non-randomized, and single arm study evaluating the outcomes of TGL in eyes with a preoperative BCVA of 20/20. We included 50 eyes of 50 patients who presented to the Hashmanis Hospital, Pakistan and were followed for six months postoperatively. All … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Although some recent studies have achieved results similar to those obtained in the FDA trial, 30,31 some of the authors of this report (MCL, TPL), as well as several other investigators, [32][33][34] have been unable to obtain the excellent postoperative visual acuities obtained during the FDA trial when the same treatment protocol was applied to eyes encountered in routine clinical practice. Various alternative strategies have been proposed, therefore, to determine the appropriate laser entry for the Treatment sphero-cylindrical refraction.…”
Section: Discussionmentioning
confidence: 54%
“…Although some recent studies have achieved results similar to those obtained in the FDA trial, 30,31 some of the authors of this report (MCL, TPL), as well as several other investigators, [32][33][34] have been unable to obtain the excellent postoperative visual acuities obtained during the FDA trial when the same treatment protocol was applied to eyes encountered in routine clinical practice. Various alternative strategies have been proposed, therefore, to determine the appropriate laser entry for the Treatment sphero-cylindrical refraction.…”
Section: Discussionmentioning
confidence: 54%
“…Many studies have shown excellent outcomes when planning treatment based solely on subjective manifest refractive astigmatism [9,[17][18][19][20][21][22][23]. However, only one study [9] reported differences between manifest astigmatism and topographic astigmatism.…”
Section: Discussionmentioning
confidence: 99%
“…Refractive surgery for hyperopia has been a challenge for surgeons in last few decades (1, 2). Hyperopia contributes to around 1/3 of all of refractive anomalies (3), but still the focus of corneal refractive surgery has centered primarily on myopia. Many studies have reported high level of safety and efficacy of Laser in situ Keratomileusis (LASIK) in correction of low hyperopia(up to 4 D) (1-2, 4-5).…”
Section: Introductionmentioning
confidence: 99%